2022
DOI: 10.3390/life12060863
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Spinal Cord Metastases from Differentiated Thyroid Cancer, a Case Report

Abstract: Intramedullary spinal cord metastases (ISCM) are uncommon metastases of the spinal cord. Magnetic resonance (MR) plays an important role in surgical planning when ISCM is suspected in the differential diagnosis. The incidence of ISCM is expected to increase due to the longer survival of cancer patients as well as the widespread use of MR in the diagnosis of neurological syndromes. The management of these patients is controversial because of the multiple clinical presentations and lack of controlled studies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Roberto Gazzeri [ 46 ] suggested that lung cancer is a common type of cancer that develops intramedullary metastasis of the spinal cord, and spinal cord metastasis is one of the key factors for the poor prognosis of the patients, and its treatment is mainly based on surgical resection, but it is prone to recurrence after the operation; Fabio Volpe [ 47 ] suggested in the case report on intramedullary metastasis of differentiated thyroid carcinoma that alleviating the compression of the tumor and resecting the tumor are important means, but the tumor still has the risk of metastasis; Rutula Sonawane [ 48 ] suggested that in some patients without sensory pain, the preexisting asymptomatic stage may delay the treatment of the disease and lead to paralysis or even paralysis, therefore, early diagnosis is the key to improve the prognosis of the disease, and in the case of patients with spinal cord metastasis, radiotherapy and surgery are the commonly used means, but there still exists the risk of recurrence, leading to its poor therapeutic effect. At this stage, little has been achieved in treating the progression of spinal cord metastases, and their therapeutic effects remain frustrating.…”
Section: Discussionmentioning
confidence: 99%
“…Roberto Gazzeri [ 46 ] suggested that lung cancer is a common type of cancer that develops intramedullary metastasis of the spinal cord, and spinal cord metastasis is one of the key factors for the poor prognosis of the patients, and its treatment is mainly based on surgical resection, but it is prone to recurrence after the operation; Fabio Volpe [ 47 ] suggested in the case report on intramedullary metastasis of differentiated thyroid carcinoma that alleviating the compression of the tumor and resecting the tumor are important means, but the tumor still has the risk of metastasis; Rutula Sonawane [ 48 ] suggested that in some patients without sensory pain, the preexisting asymptomatic stage may delay the treatment of the disease and lead to paralysis or even paralysis, therefore, early diagnosis is the key to improve the prognosis of the disease, and in the case of patients with spinal cord metastasis, radiotherapy and surgery are the commonly used means, but there still exists the risk of recurrence, leading to its poor therapeutic effect. At this stage, little has been achieved in treating the progression of spinal cord metastases, and their therapeutic effects remain frustrating.…”
Section: Discussionmentioning
confidence: 99%